2016
DOI: 10.5483/bmbrep.2016.49.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid decreases age-related adiposity and inflammation in mice

Abstract: Ursodeoxycholic acid (UDCA), a natural, hydrophilic nontoxic bile acid, is clinically effective for treating cholestatic and chronic liver diseases. We investigated the chronic effects of UDCA on age-related lipid homeostasis and underlying molecular mechanisms. Twenty-week-old C57BL/6 male and female mice were fed a diet with or without 0.3% UDCA supplementation for 25 weeks. UDCA significantly reduced weight gain, adiposity, hepatic triglyceride, and hepatic cholesterol without incidental hepatic injury. UDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…It has been shown that BA (ursodeoxycholic acid) ingestion decreases age-related adiposity and inflammation in mice (17). Circulating levels of BAs and composition are regulated by gut microbiota (18,19), and we found that the plasma levels of total BAs were significantly and inversely correlated with HOMA-IR in a multiple regression analysis.…”
Section: Discussionsupporting
confidence: 49%
“…It has been shown that BA (ursodeoxycholic acid) ingestion decreases age-related adiposity and inflammation in mice (17). Circulating levels of BAs and composition are regulated by gut microbiota (18,19), and we found that the plasma levels of total BAs were significantly and inversely correlated with HOMA-IR in a multiple regression analysis.…”
Section: Discussionsupporting
confidence: 49%
“…Thirty micrograms of protein lysate were subjected to 10% SDS-polyacrylamide gel electrophoresis followed by immunoblotting analyses (32). Antibodies were used to detect caspase-9, caspase-3, PARP (Cell signaling Technology), XBP-1, ATF4, CHOP (Santa Cruz Biotechnology), ATF6 (Abcam), and β-actin (Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…Hepatic inflammation may be a characteristic of chronic high-energy intake [25]. Furthermore, our previous data suggested that mice exhibiting an accelerated ageing phenotype and fed a Western-type diet had elevated levels of hepatic biomarkers of inflammation, including Sap [26].…”
Section: Discussionmentioning
confidence: 99%